2019
DOI: 10.18821/0016-9900-2017-96-7-614-619
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic Assessment of Health Risk Factors for Population of Megapolisis’satellite Towns by the Example of Leningrad Region

Abstract: Minor towns with population size of 50-100 thousand people are much rarely studied in regards of the ecological-hygienic assessment of human environment, in spite of the fact that they are characterized by specific ecological problems. The objective of the study was the hygienic assessment of the impact of urban environment on population health status in Tikhvin and Gatchina towns of the Leningrad region. Morbidity rate in the population of Tikhvin and Gatchina in 2005-2015, atmospheric emissions of industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Based on the results of the hygiene and environmental studies the priority environmental factors were identified that had the greatest differences in concentrations and health risk criteria [6,17,19]. The high proportion of urban residents (71,4%) are marking the impact on their health adverse environmental factors environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the hygiene and environmental studies the priority environmental factors were identified that had the greatest differences in concentrations and health risk criteria [6,17,19]. The high proportion of urban residents (71,4%) are marking the impact on their health adverse environmental factors environment.…”
Section: Resultsmentioning
confidence: 99%
“…The stages of an integrated research methodology was used for assessing the quality of life related to health [10,20], as an integral subjective measure of satisfaction with the living conditions of the habitat when exposed to risk factors [6,13]. Developed and tested a multidimensional generic questionnaire study of health-related quality of life, consisting of 15 scales [10] used for comparative analysis of the severity of the main types of functioning (social-hygienic, physical, social adaptation, recreational activities, emotional state) of urban residents.…”
Section: Methodsmentioning
confidence: 99%
“…В то же время в небольших поселениях на островных территориях, входящих в городской округ, но удаленных от крупных сетей водоснабжения, формируются специфические проблемы, зачастую не связанные с промышленной нагрузкой. Эти проблемы в существенной мере влияют на здоровье населения [6][7][8]. Например, водоснабжение на о. Русский осуществляется из скважинных водозаборов, которые обеспечивают питьевой водой небольшие населенные пункты (п. Экипажный, п. КЭТ, п. Шигино, п. Рында, п. Воевода, п. Мелководный, п. Парис, п. Подножье, п. Церковная Падь).…”
unclassified
“…Результаты и их обсуждение. Охват централизованным водоснабжением в населенных пунктах о. Русский по данным последней переписи на-__________________________ 6 Питьевая вода во всех населенных пунктах отличается пониженным содержанием солей кальция, магния и фторидов, характеризуется низкой минерализацией и жесткостью. Все показатели физиологической полноценности питьевой воды были ниже оптимальных значений.…”
unclassified
“…Environmental problems are more often addressed in large cities [5]. At the same time, small settlements on the island territories that are part of an urban district, but are remote from the major water supply networks have specific issues, often unrelated to the industrial load, but having a significant impact on public health [6][7][8]. For example, water supply on Island Russkiy is carried out from the deep well-water intakes, which provide drinking water to small settlements (settlements of Ekipajniy, KET, Shigino, Rynda, Voyevoda, Melkvodniy, Paris, Podnozhye, Tserkovnaya Pad').…”
mentioning
confidence: 99%